Nitrogen Inventories and Nitrogenase Expression Rates of a Drywood and a Subterranean Termite. (1st September 2022) - Mullins, Aaron; Scheffrahn, Rudolf; Su, Nan-Yao
Abstract: Recent research has shown that a subterranean termite ( Coptotermes formosanus Shiraki) is dependent on dietary nitrogen in order to fulfill it's nitrogen requirements for colony growth and development. Crypototermes brevis (Walker) was chosen as a model for comparison, as it has no access to dietary nitrogen outside of it's wood diet. A full nitrogen inventory before and after colony growth was conducted in order to determine the species' dependence on atmospheric N2 fixation. In addition, an expression assay was conducted for a gene encoding a nitrogenase subunit ( nifH ). Nitrogenase expression was then compared between C. formosanus and Cr. brevis . Results showed that N2 fixation was an important source of nitrogen acquisition for Cr. brevis, and nitrogenase expression was approximately four-fold higher in Cr. brevis than in C. formosanus . The nitrogenase assay used in this study is proposed as a potential tool to measure dependence on N2 fixation versus dietary nitrogen roles in diverse species of termite.